Lack of amygdala habituation to negative emotional faces in alcohol use disorder and the relation to adverse childhood experiences. (15th November 2022) - Gerhardt, Sarah; Berhe, Oksana; Moessnang, Carolin; Horning, Maibritt; Kiefer, Falk; Tost, Heike; Vollstädt‐Klein, Sabine
Abstract: Aberrant limbic circuit reactivity to negative stimuli might be related to alterations in emotion processing and regulation in alcohol use disorder (AUD). The current study tested for the first time in AUD the hypothesis of aberrant amygdala habituation to repeated aversive stimuli—a robust and reliable neuroimaging marker for emotion processing. We explored the link between deficits in habituation to adverse childhood experience (ACE), a common risk factor for impaired emotion regulation and AUD. AUD individuals ( N  = 36) and healthy controls (HC; N  = 26) participated in an observational case–control functional magnetic resonance imaging (fMRI) study. An established habituation index was used to investigate processing of aversive emotional faces of the amygdala. AUD individuals showed an overall deficit in amygdala habituation (right: t = 4.26, pFWE = 0.004; left: t = 4.79, pFWE ≤ 0.001). Amygdala habituation was significantly related to increased exposure to ACE in HC (t = 3.88, pFWE = 0.012), whereas this association was not observed in AUD individuals (T = 1.80, pFWE = 0.662). Further, a significant association between higher alcohol consumption and reduced amygdala habituation (right: R 2  = −0.356, F  = 8.736, p  = 0.004; left: R 2  = −0.309, F  = 6.332, p  = 0.015) was observed. We found novel evidence for neural alterations in emotion processing in AUD individuals, indexed by deficient amygdala habituation to negative emotional content. We replicated a prior report on a link between ACE and amygdala habituation, a well‐established environmental risk factor for mental disorders and emotion dysregulation, in our control sample. Additionally, deficient amygdala habituation related to the amount of alcohol consumption in the overall sample might indicate a short‐term substance effect. Abstract : Aberrant limbic circuit reactivity to negative stimuli relates to alterations in emotion processing and regulation in alcohol use disorder (AUD). We observed deficient amygdala habituation to negative emotional content in AUD individuals. This further related to the amount of alcohol consumption in the overall sample, possibly indicating a short‐term substance effect. We replicated a prior report on a link between ACE and amygdala habituation, a well‐established environmental risk factor for mental disorders and emotion dysregulation, in our control sample.